Characterization of Phenotypic Variation in Indigenous Chicken Populations in Lower Northern Thailand to Improve Chicken Breeding - Suphawadee Yaemkong; Siriwadee Phromnoi; Chedsada Mingchai; Touchkanin Jongjitvimol (International Journal of Zoology)
In Thailand, native chickens have a deep-rooted history of cultivation driven by diverse purposes, including food production, aesthetic appeal, exhibition, and cockfighting. Their remarkable adaptability, robustness, and resistance to diseases play pivotal roles in the evolution of chicken breeds. The study of morphological characteristics in native chicken breeds assumes significance for biodiversity conservation, sustainable agriculture, and cultural preservation. These traits not only unveil genetic diversity but also provide insights into adaptation that is crucial for the survival of native chicken populations in varied environmental conditions. The primary aim of this extensive research, conducted from June 2020 to May 2023, is to elucidate the morphological traits of six indigenous chicken breeds in Thailand’s Uttaradit province. The research methodology involved the purposive selection of a research group from chicken farms with a minimum of 5 individuals, followed by a random selection of 20 names meeting specific criteria. The resulting group comprised 134 individuals from Khiew Phalee, Thao Thong, Lueng Hang Khao, Chee, Pra Dhu Hang Dam, and Jae species. The study’s findings highlighted significant differences in eight qualitative morphological characteristics among the distinct chicken breeds, including comb type, beak color, neck plumage color, back plumage color, wing plumage color, long curved tail color, back tail color, and shank color p < 0.01. Moreover, a correlation between body size and sex-specific structures across breeds was discovered, with male chickens exhibiting significantly greater body weight, size, wing length, upper and lower shank length, and toe length than females p<0.0001. Notably, the majority of native chickens displayed the walnut (Hin) beak type, except for Jae chickens, which exhibited the single (Jak) type. Beak colors ranged from blackish-green to ivory, while each breed showcased unique plumage, tail, and shank colors, coupled with varying body sizes. This comprehensive study, covering both qualitative and quantitative parameters, emphasizes the morphological diversities among the six native chicken breeds. The derived data serve as a valuable resource for refining or developing chicken breeds in alignment with the Standard of Perfection for Thai Native Chickens, catering to the evolving needs of the market.